Berry, berry good - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Almost since the beginning of time, people have been making wines from all sorts of plants, and not just from grapes but also from wild and cultivated berries. The wine of the Marula berry is much loved throughout eastern and southern Africa, but it...